The futile mission of voluntary registers. (November 2015) - Casey, Amanda
Clinical physiologists have a vital role to perform in the diagnosis and treatment of patients. They perform sensitive and invasive procedures such as assessments and adjustments of pacemakers, internal ultrasounds and endoscopies, and lung function tests. Despite the risky nature of their work, clinical physiologists fall outside the scope of statutory regulation and are currently only subject to regulation by a voluntary register held by the Registration Council for Clinical Physiologists. While the Registration Council for Clinical Physiologists strives to maintain a register which sets a high practicing standard and which can hold practitioners to account, the nature of voluntary registration means the Registration Council for Clinical Physiologists lacks the statutory power to ensure practitioners comply with the correct processes and requirements and has no authority to discipline clinicians who practice negligently. This means that incompetent practitioners remain practically unaccountable for their actions, leaving patients without much needed protection, and putting their safety at serious risk. Over the past decade, statutory regulation has been recommended on a number of separate occasions by experts including the Health and Care Professions Council, and yet today, the workforce still exists outside the umbrella of professional oversight and scrutiny.